3-Substituted 2-isocyanopyridines as versatile convertible isocyanides for peptidomimetic design. Issue 56 (15th June 2021) - Hollanders, Charlie; Elsocht, Mathias; Van der Poorten, Olivier; Jida, Mouhamad; Renders, Evelien; Maes, Bert U. W.; Ballet, Steven
Abstract : We report the use of 3-substituted 2-isocyanopyridines as convertible isocyanides in Ugi four-component reactions. The N -(3-substituted pyridin-2-yl)amide Ugi products can be cleaved by amines, alcohols, and water with Zn(OAc)2 as catalyst. Abstract : We report the use of 3-substituted 2-isocyanopyridines as convertible isocyanides in Ugi four-component reactions. The N -(3-substituted pyridin-2-yl)amide Ugi products can be cleaved by amines, alcohols, and water with Zn(OAc)2 as a catalyst. In addition, the applicability of the method was demonstrated in constrained di-/tripeptides bearing acid and base sensitive protective groups obtained via Ugi-4CR post-condensation modifications.